Neural Adaptation Provides Evidence for Categorical Differences in Processing of Faces and Chinese Characters: An ERP Study of the N170 - Fu, Shimin (Public Library of Science, 2012)
Whether face perception involves domain-specific or domain-general processing is an extensively debated issue. Relative to non-face objects and alphabetical scripts, Chinese characters provide a good contrast to faces because of their structural configuration, requirement for high level of visual expertise to literate Chinese people, and unique appearance and identity for each individual stimulus. To examine potential categorical differences in their neural processing, event-related potentials (ERPs) were recorded to blocked face and Chinese character stimuli. Fast adaptation method was applied to better control for the low-level stimulus difference between faces and Chinese characters. Participants were required to respond to the color of the outer frame in which these stimuli were presented, at either a fast (ISI 650 ms) or slow (ISI 1300 ms) rate, and with an orientation that was either the same or alternated between upright and inverted. Faces elicited a larger and later N170 relative to characters, but the N170 was more left-lateralized for characters relative to the faces. Adaptation-by-rate and adaptation-by-orientation effects were observed on the amplitude of N170, and both were more pronounced for faces relative to characters. Inverted stimuli elicited a later N170 relative to upright stimuli, without amplitude change, and this inversion effect was more pronounced for faces relative to characters. Moreover, faces elicited a larger and later P1 and a larger adaptation-by-rate effect on P1 relative to characters. The adaptation-by-orientation effect was illustrated by a larger P1 under the same relative to the alternated orientation condition. Therefore, evidence from the amplitude and the lateralization of N170, the stimulus inversion effect on N170 latency, and the neural adaptation between faces and Chinese characters on P1 and N170 components support the notion that the processing of faces and Chinese characters involve categorically different neural mechanisms.